Spin-state transition, magnetism and local crystal structure in Eu1-xCaxCoO3-δ - Vasiliev, A. N.; Vasilchikova, Tatyana M.; Volkova, Olga S.; Kamenev, Anton A.; Kaul, Andrey R.; Kuzmova, Tatyana G.; Tsymbarenko, Dmitry M.; Lomachenko, Kirill A.; Soldatov, Alexander V.; Streltsov, Sergey V.; Lin, Jiunn-Yuan; Kao, Cheng-Nan; et al. (Journal of the Physical Society of Japan, 2013)
The doping series Eu1-xCaxCoO3-δ provides a rather peculiar way to study the spin-state transitions in cobalt-based complex oxides since partial substitution of Eu3+ ions by Ca2+ ions does not increase the mean valence of cobalt but is accompanied by appearance of oxygen vacancies in the ratio δ∼ x/2. In the parent compound EuCoO3, the low spin (LS)-intermediate spin (IS) or high spin (HS) transition takes place at temperatures so high that the chemical decomposition prevents its direct observation. The substitution of Eu3+ by Ca2+ shifts the spin state transition to lower temperatures and the associated energy gap Δ in octahedrally-coordinated Co3+ ions changes from 1940 K in EuCoO3 to 1540 K in Eu0.9Ca0.1CoO2.95 and 1050 K in Eu0.8Ca0.2CoO2.9. Besides, each O2- vacancy reduces the local coordination of two neighboring Co3+ ions from octahedral to pyramidal thereby locally creating magnetically active sites which couple to dimers. These dimers form another gapped magnetic system with a very different energy scale, - D - dim - ∼3 - Ddim∼3 - K, on the background of the intrinsically non-magnetic lattice of octahedrally-coordinated low-spin Co3+ ions.